Rescued by Europe? Social and Labour Market Reforms in Italy from Maastricht to Berlusconi - Ferrera, Maurizio 1955-; Gualmini, Elisabetta (Amsterdam University Press, 2004)
As a result of its political and economic turmoil for much of the postwar period, Italy was considered the "bad seed" in the European community. Harsh ideological divisions, chronic executive instability, inefficient bureaucracy, uneven socio-economic development, organized crime, and unbalanced public finances all contributed to this negative perception of the nation. Yet a massive economic and social overhaul was launched in the 1990s as part of Italy's efforts to meet the famous Maastricht requirements in order to join the Economic and Monetary Union (EMU). This book examines the processes Italy underwent to become part of the integrated European community and skillfully analyzes the consequences of the "Maastricht process" by exploring the effect it had on governmental and social actions and modes of orientation. Rescued by Europe? offers sharp insights into the importance of welfare state reform to current Berlusconi government, and how the weakening of the European Union's constraints has renewed the resistance to further changes. Ferrera and Gualmini ultimately argue that the constraints and opportunities linked to European integration have been the driving forces behind Italy's positive expansions, yet even with these reforms, there is still a long road ahead for European integration and Italy's political future
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Jul 2019)
Keywords: Europäische Union; Geschichte 1990-2004; POLITICAL SCIENCE / General; Labor market -- Italy; Labor policy -- Italy; Public welfare -- Italy; Sozialpolitik; Arbeitsmarktpolitik; Italien